An Australian study of long-term hospital admissions and costs comparing patients with unintentional burns and uninjured people. Issue 1 (February 2020) - Randall, Sean M.; Wood, Fiona M.; Rea, Suzanne; Boyd, James H.; Duke, Janine M.
Highlights: Burn patients have 2.48-times post-burn hospitalisations than uninjured. Burn patients spend 6-times longer in hospital post-burn than uninjured. Post-burn hospital costs are 2.77 times higher than for uninjured. Abstract: Background: The objective of this study was to describe and quantify the long-term hospital service use (HSU) after burn injury and associated costs in a population-based cohort of patients with unintentional burns and compare with uninjured people. Methods: This retrospective population-based cohort study analysed de-identified linked health administrative data of all unintentional burns patients (n = 10, 460) between 2000 and 2012 in Western Australia and a matched uninjured comparison cohort (n = 42, 856). HSU after burn injury (annual admission counts and cumulative length of stay) was examined. HSU costs were based on the Australian Refined Diagnosis Related Groups (AR-DRGs) code on each record. Generalised linear models were used to examine and quantify associations between burn injury and long-term HSU and associated costs. Results: There were 48, 728 hospitalisations after burn occurring within the study period in the burn cohort; in the uninjured comparison cohort, there were 53, 244 post-study index hospitalisations. Of those in the burn cohort, 63.9% (n = 6828) had a further hospitalisation after burn injury; this compared with 40.4% (n = 17, 297) in the uninjured cohort. After adjustment for socio-demographic and pre-existing health conditions the burn cohort had 2.48 times the hospitalisation rate compared to the uninjured cohort (95% CI: 2.33–2.65). The cost of post-index hospitalisations in the burn cohort totalled to AUS248.3 million vs AUS240.8 million in the uninjured cohort. After adjustment, the burn cohort had hospital costs 2.77 times higher than the uninjured controls (95% CI: 2.58–2.98). Conclusions: After adjustment for covariates, burn patients experienced greater hospital use for a prolonged period after the initial injury compared with uninjured people. The mean cost per episode of care was generally higher for members of the burn cohort compared to the uninjured cohort indicating either more complicated admissions or admissions for more expensive conditions.